Clinical study and management of non-thyroidal neck swellings - Athavale, Virendra; Balasubramanian, Sree Kumar; Tonape, Trupti; Khandalkar, Shivamurti; Ramesh, Keerti; Gogineni, Jyotsna (International Surgery Journal, 2019)
Background: Swellings in the neck are common and are encountered frequently in General Surgery. A diagnosis may be possible based on clinical examination alone but, investigations are required to clarify the diagnosis and, to exclude a diagnosis of malignancy. With this background, the present study is conducted in an effort to find out the causes for non-thyroidal neck swellings, and to assess the various investigations and management available for treating these neck swellings. Methods: The study was conducted on newly diagnosed non thyroidal neck swelling cases coming to the Dept. of General Surgery, ENT, Oro- Maxillofacial and Pulmonary Medicine (OPD and IPD), Dr. D. Y. Patil Medical College, Hospital and Research Centre, Pimpri, Pune. The study was conducted from July 2017 to July 2019. Data collection included history taking, clinical examination, and radiological investigation and histopathological examination by specific pathologist throughout the study. After confirmation of diagnosis, patients were subjected to further management. Results: Among 100 patients, male to female ratio was 1:1. The Mean age of the participants is 40.41±12.85 years. There was statistically significant association between tobacco addiction and malignant neck swelling. Considering HPE as gold standard, the sensitivity and specificity of fine needle aspiration cytology (FNAC) diagnosis is 81.8% and 100% respectively. Conclusions: The overwhelming amount of possible diseases linked to a swelling in the neck, makes it of utmost importance to follow a strict protocol for appropriate diagnosis making and prompt treatment so as to prevent diagnostic delay.